PROACTIVE WORK BEHAVIOR OPTIMIZATION THROUGH ENTREPRENEURIAL LEADERSHIP: TRUST IN LEADER MEDIATION TEST - Iqbal Arraniri; Heni Susilawati; Deri Prayudi (JURNAL ILMIAH EDUNOMIKA, 2024)
The phenomenon and research gaps in Indonesian entrepreneurial behavior and activity were the driving forces behind this study. The SMEs to successfully accomplish its objectives amid unpredictable circumstances, had to be completely cognizant of trust of the employee in leader could boost proactive work behavior that lead to improved output. This investigation sought to evaluate the effect of Entrepreneurial Leadership (EL) on Trust in Leader (TL), the impact of EL on Proactive Work Behavior (PWB), the impact of TL on PWB and the impact of EL using TL as an intervening variable on PWB. Data for this study came from 150 Indonesian SMEs, by distributing questionnaires. Using the regression equation and the causal step mediation test from Baron & Kenny. Keywords: Entrepreneurial leadership; Proactive work behavior; SMEs; Trust in leader